Trigonella selcuk-bayraktarii (Fabaceae), a new species from Turkey - Ilçim, Ahmet; Kocabaş, Yusuf Ziya (Phytotaxa, 2023)
Trigonella selcuk-bayraktarii İlçim (Fabaceae) is described from Kahramanmaraş Turkey. The new species is endemic and grows on steppes at an elevation of 650–750 m. The species is compared morphologically to the releated species Trigonella kotschyii considering also pollen and seed micromorphology. In addition ecology, habitat, conservation status.